2002
DOI: 10.1097/00007632-200209010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Possible Roles of CTGF/Hcs24 in the Initiation and Development of Ossification of the Posterior Longitudinal Ligament

Abstract: According to the study results, CTGF/Hcs24 may not only be an important factor in the development of endochondral ossification in OPLL, but may also be responsible for initiating osteogenesis in spinal ligament cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 14 publications
0
28
2
1
Order By: Relevance
“…Fibroblasts cells can differentiate into osteoblasts or osteocytes [4,8,9,12,24,28]. This differentiation should be accompanied by an upregulation of several marker genes related to bone formation, such as OCN, ALP and COL I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibroblasts cells can differentiate into osteoblasts or osteocytes [4,8,9,12,24,28]. This differentiation should be accompanied by an upregulation of several marker genes related to bone formation, such as OCN, ALP and COL I.…”
Section: Discussionmentioning
confidence: 99%
“…These two processes might differ in terms of the speed of bone formation [6,31]. Although several studies have investigated the osteogenetic characteristic of the spinal ligament fibroblasts from OPLL patients, the intracellular signaling pathways still remain unclear [4,8,9,12,24,28].…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear why thoracic myelopathy more often develops in middleaged people compared to cervical myelopathy patients. OLF and OPLL, the major causes of thoracic myelopathy, might be associated with some genetic factors (Koga et al 1998;Yamamoto et al 2002). The thoracic spine is naturally kyphotic and the spinal cord runs anterior of the spinal canal, which suggests the cord is more easily damaged from the anterior side.…”
Section: Discussionmentioning
confidence: 99%
“…Recent molecular genetic studies have identified several candidate genes that are differentially expressed in OPLL cells compared to normal ligament cells (15,16): reports suggest an increase in collagen, type VI, alpha 1 (Col6a1) (17,18); collagen type XI alpha 2 (Col11a2) (19,20); nucleotide pyrophosphatase (NPPS) (21 -24); leptin receptor (22); transforming growth factor-beta 1 (TGF-β1) (25 -27); promyelotic leukemia zinc finger (PLZF) (28,29); Tumor necrosis factor-alpha-stimulated gene 6 (TSG-6) (29); connective tissue growth factor (CTGF) (12); prostaglandin I 2 (PGI 2 ) (13) and endothelin-1 (30), amongst others. However, thus far, genetic factors have not been statistically linked to DISH or OPLL, most likely owing to the complexity of these diseases.…”
Section: Introductionmentioning
confidence: 99%